As cirurgias estéticas na sociedade de consumo: análise psicossocial das metamorfoses do corpo - Lopes, Janara Pinheiro (2008)
Nowadays, science and communication discourses propagate ideal patterns for thinness, beauty, youngness and health, which are subtly imposed by “wellness industry”. It fosters the capitalist logic of body, that is seen as a “consumption object”, submitted to market exigencies. Medical and media discourses happen to be referential to contemporary subjects, the former based on bodies perfection and the latter based on consumption and embellishment. The current study received an interdisciplinary outlook, since it exchanges ideas with Social Psychology, Psychoanalysis, Anthropology, History and Sociology. The research approaches body within its inner complexity as a social, singular, psychological, organic and cultural entity. In such sense, an intervention in its organic dimension, as aesthetic surgery, does not happen detached from its other dimensions, since all of them are intimately engaged. This study aims at investigating social and subjective senses of metamorphosed bodies of women who were repeatedly submitted to aesthetic surgeries, considering consumption society’s current context. Body is being target of promises of full completeness and satisfaction, mostly egress from media and science. However, suffering cannot be fully expurgated, even though wellness and the idea of a perfect body are targets of current market. That is why this research analyses in addition experiences of psychological suffering related to recurrent aesthetical surgeries and their psychosocial implications. The study, which followed a qualitative approach, interviewed seven women, trough semi-structured interviews, and arranged reports, as well as researcher placed them into three analysis categories: the contraposition involving “out of oneself” and “inside of oneself”, the contradiction between suffering and happiness, and, besides, the body, legitimated by “beauty and health industries”. The research points that, within consumption context, body takes the place of object, but, hearing women, the researcher, as a psychologist, attempted to a “subject body”, as Psychoanalysis introduces, which comprises a history and a singularity. Such idea of “subject body” is strongly opposed to the conception of “object body”, which discourses aiming at massifying subjective experience adopt. Such discourses try to hide things that differentiate each individual, since singularity has been often menaced by massifying forces which aim to standardize, especially on capitalist interests. The study argues that it does not undervalue Medicine conquests, mainly in the concerning to techno-scientific advances related to aesthetic surgeries, but it highlights possible excesses, or even to carry out such procedures, without a subjective implication, a sense attribution and a critical reflection. So, this work aims at contributing to health and advertising areas in their interfaces with Social Psychology and Psychoanalysis, triggering studies and interdisciplinary interventions